2008
DOI: 10.1177/1742395308097863
|View full text |Cite
|
Sign up to set email alerts
|

`Recovery' and current mental health policy

Abstract: This article examines a central plank of current mental health policy--'recovery'. The latter is being used increasingly as a harbinger of progress, when discussing improvements in service quality and social inclusion. Mainly using Britain as a case study, different usages of the term are considered on the part of three main interest groups: traditional biomedical psychiatrists; social psychiatrists emphasizing social skills training; and dissenting service users. These different usages suggest that 'recovery'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(57 citation statements)
references
References 23 publications
0
53
0
4
Order By: Relevance
“…Confusion between 'clinical recovery' and the 'recovery approach' may lead to clients and carers having unrealistic expectations of what is possible for them or may involve practitioners colluding with a denial of illness (Care Services Improvement Partnership, Royal College of Psychiatrists and Social Care Institute of Excellence.2007). It has also been suggested that 'recovery' is a 'polyvalent concept', in other words can be defined in many different ways and for many 6 different purposes (Pilgrim, 2008). These concerns though do appear to be mainly about differences in definition and/or concerns about how the approach may be applied rather than the approach itself.…”
Section: The Recovery Approachmentioning
confidence: 99%
“…Confusion between 'clinical recovery' and the 'recovery approach' may lead to clients and carers having unrealistic expectations of what is possible for them or may involve practitioners colluding with a denial of illness (Care Services Improvement Partnership, Royal College of Psychiatrists and Social Care Institute of Excellence.2007). It has also been suggested that 'recovery' is a 'polyvalent concept', in other words can be defined in many different ways and for many 6 different purposes (Pilgrim, 2008). These concerns though do appear to be mainly about differences in definition and/or concerns about how the approach may be applied rather than the approach itself.…”
Section: The Recovery Approachmentioning
confidence: 99%
“…Treatment no longer aims at symptom remission, but is conceptualised in terms of skills training to prevent relapses Health and maximise social integration. Professional intervention, however, still remains a central requirement for recovery (Pilgrim, 2008).…”
Section: The Experience Of Mental Distressmentioning
confidence: 99%
“…In this line of thought, recovery is conceptualised as total or partial cure, or as 'recovery from' mental illness (Davidson and Roe, 2007). This notion is firmly based on the biomedical model, as treatment remains the key determinant of recovery (Pilgrim, 2008).…”
Section: The Experience Of Mental Distressmentioning
confidence: 99%
“…Some research suggests, for example, that clinical definitions of recovery may exist in the minds of consumers (Paquette & Navarro, 2005;Piat, Sabetti, & Bloom, 2009 forthcoming;Smith, 2000;Sullivan, 1994). Pilgrim (2008) distinguishes three positions adopted by mental health consumers in relation to the discourse around recovery: 1) acceptance of the biomedical, or "recovery from", perspective; 2) a "social recovery" perspective where consumers reject psychiatry altogether; and 3) a middle ground where consumers commit to "user involvement" in an effort to reform the system (2008: 299). Whatever position consumers adopt, most would agree with Lunt (2000) that ".…”
mentioning
confidence: 99%